Visceral adiposity measures are strongly associated with cardiovascular disease among female participants in Southwest China: A population-based prospective study - Wang, Yingying; Zhao, Xiaodeng; Chen, Yun; Yao, Yuntong; Zhang, Yixia; Wang, Na; Liu, Tao; Fu, Chaowei (Frontiers in Endocrinology, 2022)
Background and Aims Controversy remains regarding the prediction effects of different adiposity measure indicators for the risk of cardiovascular disease (CVD). Our study aimed to assess the associations of three traditional anthropometric indicators, including waist circumference (WC), waist-to-height ratio (WHtR) and body mass index (BMI), as well as three non-traditional anthropometric indicators, including Chinese visceral adiposity index (CVAI), lipid accumulation product (LAP) and body shape index (ABSI) with the risk of CVD among Southwest Chinese population. Methods Our study was based on the Guizhou Population Health Cohort Study (GPHCS) conducted during 2010 to 2020. Totally 9280 participants were recruited from 12 areas in Guizhou Province, China, from November, 2010, to December, 2012, and followed up for major chronic diseases until December, 2020. And 7837 individuals with valid data were included in this analysis. The gender-specific associations of WC, WHtR, BMI, CVAI, LAP and ABSI with CVD were evaluated using cox proportional hazards models. Receiver operating characteristic (ROC) curve analysis was used to estimate the prediction powers of different indicators for CVD. Results No association of six indicators with CVD was observed among male. Female with either WC-based central obesity (HR: 1.82, 95%CI: 1.12-2.97) or WHtR-based central obesity (HR:1.68, 95%CI: 1.07-2.64) had a higher risk of CVD, after adjusted for age, area, ethnic group, smoking, alcohol drinking, MET, previous history of diabetes, hypertension and dyslipidemia, medication use and nutraceutical intake. Compared with female in the lowest quartile (Q1), female in the highest quartile (Q4) of WHtR (HR:2.24, 95%CI: 1.17-4.27), CVAI (HR:3.98, 95%CI: 1.87-8.49) and ABSI (HR:1.94, 95%CI: 1.06-3.52) had an increased risk for incident CVD. CAVI showed the maximum predictive power of CVD with the biggest AUC of 0.687 (95%CI:0.654-0.720) compared to other indicators in female. Conclusions Visceral adiposity measures, especially CVAI, are stronger predictive indicators of CVD among female not male in Southwest China. Different anthropometric indexes are warrant to be combined to comprehensively assess health risks.